2013
DOI: 10.1051/0004-6361/201321609
|View full text |Cite
|
Sign up to set email alerts
|

21-cm absorption from galaxies atz~ 0.3

Abstract: We report the detection of 21-cm absorption from foreground galaxies towards quasars, specifically z gal = 0.3120 towards SDSS J084957.97+510829.0 (z qso = 0.584; Pair-I) and z gal = 0.3714 towards SDSS J144304.53+021419.3 (z qso = 1.82; Pair-II). In both the cases, the integrated 21-cm optical depth is consistent with the absorbing gas being a damped Lyman-α (DLA) system.In the case of Pair-I, strong Na i and Ca ii absorption lines are also detected at z gal in the QSO spectrum. We identify an early-type gala… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 59 publications
3
39
0
Order By: Relevance
“…Because the impact parameter is small, we can, however, expect this extinction to be similar to that in the star-forming region as evidenced in e.g. Gupta et al (2013).…”
Section: Dependence On Dustmentioning
confidence: 92%
“…Because the impact parameter is small, we can, however, expect this extinction to be similar to that in the star-forming region as evidenced in e.g. Gupta et al (2013).…”
Section: Dependence On Dustmentioning
confidence: 92%
“…Gupta et al (2013) reported a weak correlation between impact parameter and τ dV , with a Spearman rank coefficient of r = −0.3. Adding our two new systems and two systems from the literature that Gupta et al (2013) did not consider (J074110.85+311154.7 and KAC2002), we find a slightly higher value of r = −0.39, with an associated significance level of 0.81.…”
Section: Low Redshift Galaxy-quasar Pairsmentioning
confidence: 99%
“…We somewhat arbitrarily adopted a redshift limit of z < 0.5 to include the two systems recently presented in Gupta et al (2013), and the system at z = 0.43 identified by Kanekar, Athreya & Chengalur (2002). Gupta et al (2013) reported a weak correlation between impact parameter and τ dV , with a Spearman rank coefficient of r = −0.3. Adding our two new systems and two systems from the literature that Gupta et al (2013) did not consider (J074110.85+311154.7 and KAC2002), we find a slightly higher value of r = −0.39, with an associated significance level of 0.81.…”
Section: Low Redshift Galaxy-quasar Pairsmentioning
confidence: 99%
“…The points are binned via the Kaplan-Meier estimator, giving the maximum-likelihood estimate based upon the parent population (Feigelson & Nelson 1985), from which we see no overwhelming bias in the survey sensitivity between the Mgii absorbers and DLAs. Darling et al (2004); Curran et al (2005Curran et al ( , 2007aCurran et al ( ,b,c, 2010; York et al (2007); Gupta et al (2009aGupta et al ( ,b, 2012Gupta et al ( , 2013 …”
Section: Line Strengths Of the Intervening H I 21-cm Absorbersmentioning
confidence: 99%